The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1128/iai.54.3.869-875.1986
|View full text |Cite
|
Sign up to set email alerts
|

Granuloma formation and hemopoiesis induced by C36-48-mycolic acid-containing glycolipids from Nocardia rubra

Abstract: As previously reported (I. Yano, I. Tomiyasu, S. Kitabatake, and K. Kaneda, Acta Leprologica 2:341-349, 1984), Nocardwa rubra, one of the nonpathogenic actinomycetes, possesses three classes of mycolic acidcontaining glycolipid, i.e., glucose mycolate, trehalose dimycolate, and trehalose monomycolate. The carbon chain length of their mycolic acids is shorter (C_3&,a) than that in mycobacteria (longer than C70), and the glycolipid consists of only a-mycolic acid. One intravenous administration of 500 ,Ig of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Part of the pathological changes induced by viable bacteria might be ascribed to some factor other than glycolipid of R. equi. Granuloma-forming capacity of glycoplipid from R. equi seems to be comparable to that observed in glycolipid from Nocardia (10). Nocardia species produce various glycolipids containing mycolic acid ranging from C30 to C60, and it is shown that granuloma-forming activity is small if mycolic acid is shorter than C40.…”
Section: Discussionsupporting
confidence: 51%
“…Part of the pathological changes induced by viable bacteria might be ascribed to some factor other than glycolipid of R. equi. Granuloma-forming capacity of glycoplipid from R. equi seems to be comparable to that observed in glycolipid from Nocardia (10). Nocardia species produce various glycolipids containing mycolic acid ranging from C30 to C60, and it is shown that granuloma-forming activity is small if mycolic acid is shorter than C40.…”
Section: Discussionsupporting
confidence: 51%
“…Initially, cord factor was considered to be a potent virulence factor since it had been isolated from the highly virulent M. tuberculosis strain, which grows as a serpentine cord on the surface culture (4). However, it was subsequently found that cord factor and analogous glycolipids exist widely among virulent and avirulent Mycobacterium, Nocardia, Rhodococcus and Corynebacterium (1,22), and furthermore, that they possess various immunostimulatory properties including granuloma-forming activity, adjuvant activity, anti-tumor activity and non-specific infection prevention activity (1,3,16,(26)(27)(28)30). Thus, immunologically, cord factor seems to stimulate cellular immunity (Th 1 response dominant) as an adjuvant and to be non-specific as an antigen.…”
Section: Discussionmentioning
confidence: 99%
“…equi produces glycolypids containing different mycolic acid structures ranging widely from C,, to C,, [28,30]. Purified glycolipids of rhodococci and Nocardia rub-a have shown various biological activ- ities, including granuloma formation and hemopoiesis [28,31,32]. Gotoh et al [28] showed that the carbon length of mycolic acid from R. equi is critical in granuloma formation in murine liver.…”
Section: Listeria Monocytogenesmentioning
confidence: 99%